Mechanisms of Reactive Oxygen Species Generated by Inorganic Nanomaterials for Cancer Therapeutics - Zhang, Lizhen; Zhu, Chengyuan; Huang, Rongtao; Ding, Yanwen; Ruan, Changping; Shen, Xing-Can (Frontiers in Chemistry, 2021)
Recently, inorganic nanomaterials have received considerable attention for use in biomedical applications owing to their unique physicochemical properties based on their shapes, sizes, and surface characteristics. Photodynamic therapy (PDT), sonodynamic therapy (SDT) and chemical dynamic therapy (CDT), which are cancer therapeutics mediated by reactive oxygen species (ROS), have the potential to significantly enhance the therapeutic precision and efficacy for cancer. To facilitate cancer therapeutics, numerous inorganic nanomaterials have been developed to generate ROS. This mini review provides an overview of the generation mechanisms of ROS by representative inorganic nanomaterials for cancer therapeutics, including the structures of engineered inorganic nanomaterials, ROS production conditions, ROS types, and the applications of the inorganic nanomaterials in cancer PDT, SDT and CDT.